High-temperature and abrasion resistance of self-compacting mortars incorporating binary and ternary blends of silica fume and slag - Yon, Merve Sahin; Arslan, Furkan; Karatas, Mehmet; Benli, Ahmet (Elsevier Sci Ltd, 2022)
Researchers from all over the world have recently developed an interest in the utilization of waste materials in the concrete industry. Using silica fume (SF) and ground granulated blast furnace slag (S) to manufacture self-compacting mortars (SCMs) could be a step toward sustainable waste management and produce the unique fresh qualities needed for SCMs. This research evaluates the abrasion and high-temperature resistance of SF and S based SCMs. A total of 14 mixtures were designed by partially replacing SF and S with Portland cement (PC) including control, binary and ternary mixtures. Binary mixtures were obtained by replacing cement by SF and S at replacement rates of 5, 10, 15 and 20 % and 10, 20, 30 % by weight respectively. Ternary mixtures were determined at the rates of 5, 10, 15 and 20 % SF and 10 and 20 % S respectively. The flexural strength and compressive strength of SF and S based binary and ternary water curing SCMs samples were determined at the age of 7, 28 and 90 days at room conditions. SCMs specimens were exposed to high temperatures after 90-day water curing. Water absorption, apparent porosity, sorptivity and abrasion resistance of 28-day water cured SCMs samples was also determined. The fresh and rheological properties of SCMs was evaluated by conducting mini-slump flow and viscosity tests. Cost analysis of the SCMs were also performed. The experimental results exhibited that the flowability of SCMs mixes containing SF was reduced with the increasing rate of SF compared to control while the workability of S incorporated SCMs mixes increased with the increase of S in comparison to control mixtures. Late-age of compressive strength above 70 MPa was achieved for 20 % SF incorporated binary mixture and 15 %SF and 10 % S incorporated ternary mixture. The ternary mixture with 15 % SF and 10 % S also exhibited the best abrasion resistance and the lowest sorptivity. Overall, it can be concluded from the mechanical characteristics and abrasion resistance that ternary combination of S with SF content of especially above 10 % and can be used to manufacture self-compacting mortar with a smaller carbon footprint.
Keywords: High temperature; Self-compacting mortars; Mechanical properties; Abrasion